2007
DOI: 10.1590/s1413-70542007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do número de adultos de Trichogramma galloi Zucchi, 1988 (Hymenoptera: Trichogrammatidae) liberados em semanas sucessivas, para o controle de Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae)

Abstract: Neste trabalho, estudou-se o efeito do número de adultos de Trichogramma galloi Zucchi, 1988 liberados em semanas sucessivas, para o controle de Diatraea saccharalis (Fabricius, 1794). O experimento foi conduzido em março de 2003, com a cultivar SP 79-1011, de quatro meses de idade. Adotou-se o delineamento experimental inteiramente casualizado. Foram demarcadas quatro subáreas de 400 m² cada (20 m x 20 m), eqüidistantes 20 m. Cada parcela foi infestada artificialmente uma vez por semana com 20 casais de D. sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In other cases, greater density of parasitoids can increase intraspecific competition and reduce parasitism, as reported for other eulophid species, e.g., P. elaeisis and T. diatraeae (Pereira et al 2010, Favero et al 2013. However, even in the field, the probability for a parasitoid to find a non-parasitized host decreased with the parasitoid density increases, as observed for T. galloi and D. saccharalis eggs (Broglio-Micheletti et al 2007).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In other cases, greater density of parasitoids can increase intraspecific competition and reduce parasitism, as reported for other eulophid species, e.g., P. elaeisis and T. diatraeae (Pereira et al 2010, Favero et al 2013. However, even in the field, the probability for a parasitoid to find a non-parasitized host decreased with the parasitoid density increases, as observed for T. galloi and D. saccharalis eggs (Broglio-Micheletti et al 2007).…”
Section: Discussionmentioning
confidence: 55%
“…However, larvae after the first or second molt (3-8 days) burrow into the stalk, where they remain during the whole development (40-45 days) gaining partial protection from sprays (Antigo et al 2013). In Brazil, the egg parasitoid Trichogramma galloi Zucchi and the larval endoparasitoid C. flavipes have been widely used against sugarcane borers (Broglio-Micheletti et al 2007, Vacari et al 2012. Nevertheless, populations of Diatraea spp.…”
Section: Introductionmentioning
confidence: 99%
“…2000). In that sense, Broglio‐Micheletti et al. (2007) tested the release of 100 000, 200 000 and 250 000 adults of Trichogramma galloi Zucchi per hectare of sugar cane during successive weeks on the control of Diatraea saccharalis Fabricius and found that the best release rates were between 150 000 and 175 000 parasitoids adults per hectare.…”
Section: Discussionmentioning
confidence: 99%
“…Esse comportamento dificulta seu manejo, pois o inseto fica protegido contra as pulverizações de inseticidas. O controle biológico de D. saccharalis é extremamente importante, especialmente quando se emprega o endoparasitoide larval Cotesia flavipes (Cameron) (Hymenoptera: Braconidae) (BROGLIO-MICHELETTI et al, 2007). No entanto, Pinto et al (2003) relataram que o controle utilizando o parasitoide de ovos Trichogramma, tem como grande vantagem o fato desse inimigo natural poder reduzir a população da praga antes que algum dano seja causado à cultura.…”
Section: Introductionunclassified